Pengalaman Ibu Dalam Merawat Anak Autis Usia Sekolah - Murniati - Noor; Ganis - Indriati; Veny - Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Abstract The purpose of this study was to known mother experience in caring school-age children with autism. The research method was qualitative with phenomenological approach to described mother experience in dealing with any problems in the treatment of children with autism. This study was conducted in three School of Children with Special Needs Pekanbaru involved 5 participants that taken by purposive sampling method. The process of data collection using interviews with a semi-structured interview guide, field notes and recording devices. The research found five theme such as: experiences mother when children diagnosis autism, mother treatment for children autism, like or dislike in treatment children autism, solving of problem in treatment children autism, supporting for mother that acquired. The research recommends to school of children with special need to parents with information about the strategies and tips for taking care of autistic children based on experiences of parents. Keywords: Autism, parents experience